On equivalence of semigroup identities - Macedońska, O.; Żabka, M. (MATHEMATICA SCANDINAVICA, 2001)
For a given relation ρ on a free semigroup F we describe the smallest cancellative fully invariant congruence ρ^ containing ρ. Two semigroup identities are s-equivalent if each of them is a consequence of the other on cancellative semigroups. If two semigroup identities are equivalent on groups, it is not known if they are s-equivalent. We give a positive answer to this question for all binary semigroup identities of the degree less or equal to 5. A poset of corresponding varieties of groups is given.